ANALISIS KETERAMPILAN BERBICARA SISWA KELAS V PADA PEMBELAJARAN BAHASA INDONESIA SDN KARANG TENGAH 06 - Dini Utami; Boy Dorahman; Dilla Fadhillah (Jurnal Dedikasi Pendidikan, 2023)
This study aims to 1) find out the speaking skills of fifth grade students at SDN Karang Tengah 06, 2) find out the factors that influence speaking skills in learning Indonesian for fifth grade students at SDN Karang Tengah 06. This research uses qualitative methods so that the data presented is in the form of analysis, the subjects used in this study amounted to 34 students. Data collection techniques used are observation, interviews, tests, and documentation. The results of the study can be concluded 1) in aspects of speaking skills possessed by VB class students at SDN Karang Tengah 06 they are still lacking in the intonation, courage, and demeanor sections, for aspects of pronunciation, vocabulary and memorization are in the good category but still need to be improved again so that later students can master all aspects of speaking skills well and even very well. 2) the factors that affect students' speaking skills consist of linguistic factors, such as students' lack of knowledge about how to pronounce, intonation, vocabulary or sentences properly and correctly, while non-linguistics such as students' lack of courage when speaking or reciting rhymes in front of the class, lack of students' knowledge about how to have a good attitude when speaking or reciting rhymes in front of the class, and still lack of fluency or mastery of topics owned by VB class students at SDN Karang Tengah 06